The Physicochemical Properties of Goat Skin Gelatin at Different Ages With the Use of Lactobacillus plantarum and Acetic Acid as a Pretreatment - Hasma Hasma; Effendi Abustam; Ratmawati Malaka; Muhammad Irfan Said; Asmuddin Natsir (Faculty of Animal Science, Hasanuddin University, Makassar, Indonesia, 2020)
ABSTRACT Pretreatment of chemical acids using organic chemicals has been widely applied, while pretreatment using microbial Lactobacillus plantarum to form ossein in goat skin has not been done much. Application of Lactic Acid Bacteria (LAB) microbial species L. plantarum is thought to affect health and environment friendly. This study aims to determine the characteristics of goat skin gelatin at different ages of L. plantarum 1uhcc pretreatment and acetic acid (CH3COOH). Each treatment was repeated 3 times. The study design used a Split Plot Design with acid source treatment as the main plot and the age of goats 1, 2 and 3 years as subplots. The results showed a very significant effect (P<0.01) between the age of the goat with gel strength, pH, viscosity and color. The highest gel strength and viscosity at 1 year of age with L.plantarum pretreatment respectively (441.37±0.78 g bloom) and (9.22±0.09 cP). Goat skin gelatin has the highest pH at 1 year of age with L.plantarum 5.24±0.16. Similarly, the effect of gelatin (P<0.05) with a brightness level (L) 76.38±1.10 and redness (a) 11.13±1.58 affect the age of goats and acidic sources while yellowish (b) 33.81±2.34 only affects the acid source. Age of goats with different acid pretreatment has an impact on the physicochemical properties of goat skin gelatin. Goat age 1 year with L.plantarum pretreatment showed optimal results.